Deciphering the cryptic species diversity of dull-coloured day geckos Phelsuma (Squamata: Gekkonidae) from Madagascar, with description of a new species - Crottini, Angelica; Gehring, Philip-Sebastian; Glaw, Frank; Harris, D. James; Lima, Alexandra; Vences, Miguel (Zootaxa, 2011)
We describe a new Phelsuma species from the relictual forest of Anja Reserve (13 km south from Ambalavao, on the central high plateau of southern Madagascar). Phelsuma gouldi sp. nov. seems to be an arboreal and possibly rockdwelling species that has been observed in the private Anja Reserve (949 m a.s.l.), and possibly near Betroka almost 160 km further south-west. The species belongs to the P. mutabilis species group and differs from the other three species of the group, P. mutabilis, P. breviceps, and P. borai by a high genetic divergence of more than 10% in the mitochondrial 16S rRNA gene, and by a combination of 7–9 subdigital lamellae under the fourth toe, 6–7 supralabials, one internasal, and numerous details of throat scalation. Phelsuma mutabilis comprises three mitochondrial clades with divergences of more than 4% in the 16S rRNA gene, but the lack of distinct morphological differences and absence of a geographical structure among these clades indicate that this pattern is currently best considered as reflecting intraspecific variability.